The share of renewable electricity in electric vehicle charging in Europe is higher than grid mix - Sabine Preuß; Robert Kunze; Jakob Zwirnmann; Jonas Meier; Patrick Plötz; Martin Wietschel (Fraunhofer-Institut für System- und Innovationsforschung ISI, 2021)
Plug-in electric vehicles (PEV) are widely considered a promising option to reduce greenhouse gas (GHG) emissions in transport. The electricity used for charging is decisive for the environmental assessment of PEV. Most studies assume the average grid mix for charging. This article provides a systematic overview of existing studies and additional data on the electricity contracts of users and charge point operators (CPO) as well as the share of renewables in the charged electricity for PEV in Europe. We combine survey data with existing studies and cover a noteworthy share of the European PEV market and CPO. Our results show that the actual share of renewables in electricity contracts for home and work charging as well as for public CPO is much higher than in the European grid mix. Despite discussions around the methodological use of contracted renewable electricity, our findings imply that many previous studies underestimated the well-to-wheel life-cycle benefits of PEV.
urn:nbn:de:0011-n-6439643
Keywords: 330